2021
DOI: 10.1093/mnras/stab3594
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mass-loss and stellar wind effects in young and old systems – I. Comparative 3D study of TOI-942 and TOI-421 systems

Abstract: At young ages, when radiation from the host star is high, and the planet is hot and inflated after formation, planetary atmospheric mass loss can be extremely strong compared to older planets. In turn, stellar winds are faster and denser for young stars compared to evolved main-sequence stars. Their interaction with escaping planetary atmospheres can substantially affect atmospheric mass loss rates, as well as the observable signatures of escaping atmospheres, with both effects expected to occur differently fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In strong extreme-UV environments, the neutral hydrogen tail that is optically thick in Lyα is quickly ionized by the stellar wind, resulting in a reduced transit depth in these wavelengths. 3D simulations (e.g., Kubyshkina et al 2022) also reinforce the importance of stellar wind interactions for the observed shape and sizes of the escaping neutral hydrogen tails.…”
Section: Hα As a Tracer For Evaporation And Temporal Atmospheric Vari...mentioning
confidence: 64%
“…In strong extreme-UV environments, the neutral hydrogen tail that is optically thick in Lyα is quickly ionized by the stellar wind, resulting in a reduced transit depth in these wavelengths. 3D simulations (e.g., Kubyshkina et al 2022) also reinforce the importance of stellar wind interactions for the observed shape and sizes of the escaping neutral hydrogen tails.…”
Section: Hα As a Tracer For Evaporation And Temporal Atmospheric Vari...mentioning
confidence: 64%
“…Another technique that aims to limit the parameter space of m  versus T in unresolved metastable He spectroscopy involves taking into account the effects of radiative heating/cooling, expansion cooling, and heat advection (see Linssen et al 2022). Ideally, one-or threedimensional hydrodynamics models (such as the ones described in Salz et al 2016;Shaikhislamov et al 2021;Kubyshkina et al 2022;) break this degeneracy by calculating the outflow temperature profile and mass-loss rates self-consistently, but they are more computationally expensive and they have other free parameters as well -such as atmospheric abundances, stellar wind strength, and planetary magnetic field strength. Our simulations of the metastable He transmission spectrum of GJ 1214 b show that, for a substellar mass-loss rate of 2.5 × 10 8 g s −1 and outflow temperature of T = 3000 K (based on the detection limits of Kasper et al 2020), the signal is detectable with NIRSpec/G140H at 5σ confidence.…”
Section: Resultsmentioning
confidence: 99%
“…Although Vissapragada et al (2022a) provides a framework to set upper limits by assuming that the outflow is solely powered by photoionization, these upper limits are not as informative for sub-Jovians as they are for hot gas giants. Self-consistent hydrodynamic simulations do not have this degeneracy, since the outflow temperatures and escape rates are set by the underlying physics of the model (e.g., Salz et al 2016;Shaikhislamov et al 2021;Kubyshkina et al 2022). The approach described by Linssen et al (2022) may also be helpful, as they rule out part of the temperature and mass-loss parameter space by calculating the temperature structure of the outflow based on a self-consistent photoionization model.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…They also discussed the possibility that the high velocity can be attributed to charge exchange between the ionized, fast SW ions and the neutral, slow escaping hydrogen atoms, but they did not include this process in their simulation. The interaction between the escaping atmosphere and a generic SW has also recently been studied by Shaikhislamov et al (2016), Carolan et al (2020), and Kubyshkina et al (2022) using a hydrodynamic model. They have found that a stronger SW reduces the mass-loss rate by a factor of 2.…”
Section: Introductionmentioning
confidence: 99%